British government and politics - Punnett, R. M. (London : Heinemann Educational, 1980)
This text is intended for students concerned with the institutions of British government. This edition has been thoroughly revised to provide a comprehensive, up-to-date account of the many facets of British government and politics in the 1990s.
Includes bibliographical reference and index
Keywords: Great Britain; Politics and government